Efektivitas Kebijakan Sistem Zonasi Oleh Dinas Pendidikan Terhadap SMA Negeri 3 Tanjungpinang - Nadia Tika Adisti; Nurul Aulia Putri; Windi Prestiya Ananda Putri (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
School is a place to seek various knowledge to develop the abilities of students. The government prepares a compulsory education program that lasts 12 years regulated in law No. 20 of 2003 concerning the National Education System. Admission of New Learners (PPDB) is the initial stage for schools to improve the quality of education. Learners, teachers, and schools are the main things in the process of continuity of teaching and learning. The Zoning System is the government's effort to separate the dichotomy between superior and non-superior schools. However, in reality, there is still unbalanced competition in this policy. There are still schools that only get a few new prospective students compared to other schools. This research uses a qualitative approach with primary and secondary data analysis methods. The effectiveness of the zoning system is based on several aspects including impact, sustainability and challenges faced. Cooperation between the government, schools and communities is needed to overcome these challenges and ensure that the zoning system can achieve the goal of equitable and quality education distribution without any reference or formula.